การค้นหายีนในกลไกการออกดอกของมะพร้าว (Cocos nucifera L.) ด้วยเทคนิค Differentially Display RT-PCR - ไทยสกุล, ศิริวรรณ; มณีประเสริฐ, ปริยา; มงคลศิริวัฒนา, จรีรัตน์ (Thai Journal of Science and Technology, 2019)
Abstract To identify novel genes involved in controlling flowering transition of coconut, DDRT-PCR (differentially display RT PCR) was used to compare expression of genes in somatic apical meristem (SAM) of dwarf coconut during vegetative growth phase, Vg (germination, 4, 6, 12 and 24 months of age) and reproductive phase, Rp (36 months of age). The result revealed that genes encoding adenylate kinase, DNA (cytosine-5)-methyltransferase 1b, 14-3-3 protein 6, retrotransposon RLC_Rider_Eg133H20-1, ALP1 like transposon and uncharacterized proteins (LOC105038377 and LOC105032930) were identified as up-regulated genes in reproductive phase. The expression of these candidate genes were monitored during growth and development in both dwarf (early flowering type) and tall (late flowering type) coconuts using quantitative real time PCR. The expression of those six genes, except ALP1 like, showed gradually increase during vegetative growth phase (germination, 4, 6, 12 and 24 months) and reached the highest in reproductive phase in both coconut types (36 months in dwarf and 60 months in tall types). Interestingly, ALP1 like showed dynamic expression, up-regulated during seedling and then disappeared during juvenile and up-regulated again during adult and reproductive phase. The different expression pattern between dwarf and tall coconuts was also found in which tall coconut showed delay expression. Taken its function and this result together, we proposed that shorten vegetative growth phase and early flowering of dwarf coconut was probably controlled by ALP1 like. Keywords: coconut; flowering transition; prolong vegetative growth phase; DDRT PCR (differentially display RT-PCR)